Code Switching Phenomenon in Early Childhood at PJ Global Kids Bilingual School: Causal Factors and Impacts - Diah Nur Hadiati (Jurnal Pengabdian Masyarakat Formosa, 2024)
The phenomenon of code switching in early childhood at the PJ Global Kids bilingual school is an interesting topic to study, considering the importance of mastering more than one language in the context of modern education. This study aims to identify the factors that cause code switching and its impact on children's language development. Qualitative research methods were used to explore data through in-depth interviews with teachers, parents, and direct observation in the classroom. The results showed that code switching occurs as a response to the social environment and children's communication needs. Factors such as peer influence, situational context, and language habits at home contribute significantly to this phenomenon. The impact of code switching is seen in children's increasingly developing language skills and their increasing social skills. However, there are also challenges that arise related to the consistency of language use that can affect overall language learning.